INFLUENCE OF SLOPE ANGLE ON LINEAR DIMENSIONS OF INSTRUMENT ARRAY DISPLACEMENTS IN VARIOUS ZONES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The paper considers the influence of the slope angle on the distribution of linear displacements in the instrument array. The finite element method was used for the analysis, which made it possible to perform numerical calculations and determine the nature of changes in the horizontal and vertical displacements of the rock mass with varying slope steepness. Displacement distributions are plotted in various zones of the instrument array, including the zone of the outermost state, residual strength, pre-limit and natural state. It has been established that an increase in the slope angle leads to a redistribution of stresses and displacements deep into the massif, which has a significant impact on its stability. The results obtained make it possible to more reasonably assess the stability of the sides of the quarry, predict the development of deformations, and develop preventive measures to prevent emergency geomechanical processes in the conditions of open-pit mining.
Keywords: instrument array, linear displacements, slope angle, numerical modeling